1993
DOI: 10.1121/1.407242
|View full text |Cite
|
Sign up to set email alerts
|

Vocal affect in three-year-olds: A quantitative acoustic analysis of child laughter

Abstract: Recordings were obtained of the laughter vocalizations of four 3-year-old children during three sessions of spontaneous free-play between mother and child in a laboratory playroom. Acoustic analysis was used to determine laughter durations, laughter events, F0, and harmonic characteristics, and to suggest a taxonomy of laughter types. Melodic contours were assessed from patterns of F0 change during laughter. Mean duration of laughs ranged from 200 ms to 2.0 s, but events within a laugh were usually about 200-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 26 publications
3
15
1
Order By: Relevance
“…Alternatively, use of non-central vowels might be related to intraindividual differences. Previously, it was speculated that each person has their own characteristic laughter sound [8,10,18]. This hypothesis is supported by our data, as we found that individual speakers tended to use a constant set of vowel elements, but inter-individual variability was high.…”
Section: Vowelssupporting
confidence: 81%
See 1 more Smart Citation
“…Alternatively, use of non-central vowels might be related to intraindividual differences. Previously, it was speculated that each person has their own characteristic laughter sound [8,10,18]. This hypothesis is supported by our data, as we found that individual speakers tended to use a constant set of vowel elements, but inter-individual variability was high.…”
Section: Vowelssupporting
confidence: 81%
“…[22,23]) with F0 being up to 1765 Hz for female speakers and 595 Hz for male speakers, respectively ( [1]: males (females) 1245 Hz (2083 Hz); see also [18] for children: 3200 Hz).…”
Section: Differences In Speaker Sexmentioning
confidence: 99%
“…The laughter vocalization period is composed of laugh cycles, i.e., repetitive laugh-pulses (Moore & von Leden, 1958) interspersed with pauses. There is laughter with only one or two pulses ("exclamation" laughter, "chuckle"; Nwokah et al, 1993), but studies typically report a mode of four pulses in a laugh cycle (Provine & Yong, 1991;Rothgänger et al, 1998). The upper number of pulses in a laugh cycle is limited by the lung volume, and different studies give numbers between 9 and 12 (Boeke, 1899;Provine & Yong, 1991); a laughter episode -two or more laughter bouts separated by inspirations-will have more.…”
Section: Laughter Segmentationmentioning
confidence: 99%
“…Several studies have investigated the acoustic characteristics of laughter (e.g., Bachorowski et al, 2001;Trouvain, 2003;Bickley and Hunnicutt, 1992;Rothganger et al, 1998;Nwokah et al, 1993) and compared these characteristics to speech. Of these studies, the study by Bachorowski et al (2001) is probably the most extensive one using 97 speakers who produce laugh sounds, while the other studies mentioned here use 2-40 speakers.…”
Section: Focus On Automatic Laughter Detectionmentioning
confidence: 99%